European illegal puppy trade and organised crime - Maher, Jennifer (Trends in organized crime, 2021)
Organised crime groups’ involvement in illicit markets is a common focus of law enforcement and governments. Drug, weapon, human and wildlife trafficking (and others) are all illegal activities with link to organised crime. This paper explores the overlooked illicit market of puppies. We detail the state of knowledge about the organisation of the UK puppy trade, which includes irresponsible and illegal breeding of puppies throughout Europe and their often-illegal movement into the UK. In 2017, we conducted an analysis of hundreds of online advertisements in Scotland, 12 expert interviews, a stakeholder survey of 53 participants, and 40 focus groups across Great Britain. Our data suggest an organised illicit market running in parallel to the legal trade. We speculate as to whether at some point along the supply chain organised crime groups are responsible for the suffering and death of the puppies and the economic and emotional damage to ‘consumers’. Online monitoring and physical scrutiny at the ports must be improved to reduce non-human animal abuse. People buying puppies must also be made aware that their purchase could be profiting organised crime.